Introduction to structural dynamics and aeroelasticity - Hodges, Dewey H. (Cambridge University Press, 2011)
"This text introduces structural dynamics and aeroelasticity, emphasizing conventional aircraft"-- Provided by publisher
Machine generated contents note: 1. Introduction; 2. Mechanics fundamentals; 3. Structural dynamics; 4. Static aeroelasticity; 5. Aerolastic flutter.
Keywords: Space vehicles -- Dynamics.; Aeroelasticity.; elektronické knihy; electronic books